A review on design and performance of thermomagnetic devices. (January 2018) - Kishore, Ravi Anant; Priya, Shashank
Abstract: Thermomagnetic energy harvesting technology has not received significant attention despite great potential for generating electricity from low thermal gradient near room temperature. This review summarizes the findings reported in literature covering the broad topical areas within thermomagnetic energy harvesting and provides perspective on the potential applications of this technology. The information has been organized chronologically in order to provide systematic understanding of the concepts and evolution of the device designs. Both, active and passive types of thermomagnetic energy harvesters have been included in the paper. The selection of suitable thermomagnetic material is key towards achieving an efficient energy generation device. Therefore, various material compositions have been discussed and their thermomagnetic behavior has been elucidated to provide guidance for their implementation in future devices.